Effect of sintering holding time on the properties and low-temperature degradation behaviour of manganese oxide-doped Y-TZP ceramic - Kwa S.M.; Ramesh S.; Bang L.T.; Wong Y.H.; Kelvin Chew W.J.; Tan C.Y.; Purbolaksono J.; Misran H.; Teng W.D. (Hanyang University, 2023)
The sintering of yttria-tetragonal zirconia polycrystals (Y-TZP) is commonly carried at a predefined temperature using a long holding time of 2 hours. This often has resulted in grain coarsening which affects the mechanical properties of the sintered body and low temperature degradation (LTD) behaviour of the ceramic when exposed to moist environment. In this research, the effect of using a short holding time of 1 min. during sintering coupled with small amounts (0.5 and 1 wt%) of manganese oxide, MnO2 as dopant on the mechanical properties and LTD behaviour of 3 mol% Y-TZP were investigated. The results showed that the mechanical properties improved significantly with the addition of 0.5 wt% MnO2 for the 1-min. and 12-min. holding time samples when compared to 2 hours holding time sintered at the same temperature of 1350 oC. Nevertheless, regardless of the holding time employed, the 1 wt% MnO2 addition was not effective in improving the mechanical properties and ageing resistance of Y-TZP ceramic. 2015, Hanyang University. All rights reserved.